Legal Analysis of the Handling of Non-Procedural Migrant Workers Recruited from East Nusa Tenggara (NTT) - Aminah, Indah; Tanudjaja, Tanudjaja (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the legal framework and mechanisms for handling non-procedural recruitment of migrant workers from East Nusa Tenggara (NTT), Indonesia. Despite the presence of comprehensive national laws—such as Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers and Law No. 21 of 2007 on the Eradication of Human Trafficking—the implementation remains weak at the local level. Using a normative juridical approach, this research examines statutory regulations, institutional roles, and practical challenges related to labor migration governance. The findings reveal that illegal recruitment persists due to poor law enforcement, lack of public awareness, limited economic alternatives, and institutional fragmentation. Moreover, many victims of non-procedural recruitment do not receive adequate legal aid or reintegration support upon return. This study concludes that an integrated strategy combining law enforcement, community education, and local economic empowerment is essential to prevent and resolve non-procedural labor migration. The research contributes to the discourse on migrant protection and offers practical recommendations for policy reform and institutional strengthening.